STRATEGI PENGEMBANGAN AGROWISATA PETIK STROBERI PADUSAN KECAMATAN PACET KABUPATEN MOJOKERTO - Nanda Maya Savitri; Mubarokah Mubarokah; Ida Syamsu Roidah (Yayasan Education and Social Center, 2023)
Padusan Strawberry Picking Agrotourism requires a development strategy to solve the problems faced by the COVID-19 pandemic; lack of marketing, facilities not developed, and fewer tourist attractions. This study aims to determine the overall development of agro-tourism, identify internal factors and external factors of agro-tourism, and analyze appropriate strategies in the development of Padusan Strawberry Picking Agro-tourism. The research uses the SOAR and QSPM analysis methods. The results of the research show that 1) The overall development of Padusan Strawberry Picking Agrotourism can be seen from the development of the number of visitors, attractions, accessibility, amenities, and ancillary. 2) Internal and external factors are divided into 4 groups, namely Strength and Aspiration which belong to the group of internal factors, and Opportunity and Result which belong to the group of external factors. 3) Through the stages of the IE matrix and the SOAR matrix, nine alternative strategies were obtained which were analyzed using QSPM so that a priority strategy with the highest TAS value of 6.804 was obtained, namely adding facilities to make it more complete and upgrading to be better which provides comfort for agro-tourism visitors